COMPARISON OF VISUAL ACUITY RESULTS AFTER FEMTOSECOND LASER-ASSISTED IN SITU KERATOMILEUSIS (FS-LASIK) AND SMALL INCISION LENTICULE EXTRACTION (SMILE) - Mardhiyya, Nafisa; Andrew M. H. Knoch; Emmy D. Sugiarti; Ludwig M. Tjokrovonco; Budiman (The Indonesian Ophthalmologists Association (IOA, Perhimpunan Dokter Spesialis Mata Indonesia (Perdami)), 2024)
Introduction: Two of the most popular refractive surgery methods currently used are Femtosecond Laser-Assisted In Situ Keratomileusis (FS-LASIK) which creates a flap using femtosecond laser and stromal ablation using excimer laser, and Small Incision Lenticule Extraction (SMILE), a flapless procedure in which a lenticule is extracted through a small incision. The aim of this study is to compare the visual acuity results of FS-LASIK and SMILE. Methods: This is a descriptive cross-sectional study. Data were collected from the medical record of patients who underwent FS-LASIK or SMILE procedure at Cicendo Eye Hospital, the national eye centre, in 2022. Patients were followed up at 1 day, 1 week, and 1 month postoperatively and visual acuity outcomes between the two procedures were compared. Results: A slightly higher percentage of eyes in FS-LASIK (46.6%) achieved a UCVA of 1.0 at 1 day postoperatively compared to SMILE (45.5%). At 1 week and 1 month, SMILE showed superior results with 83% and 94.6% of eyes achieving a UCVA of 1.0, meanwhile FS-LASIK had 72.2% and 86.2%. Residual refractive error at 1 month had a median of -0.6146 and -0.3125 in the FS-LASIK and SMILE groups. Conclusion: This study found better UCVA results in the FS-LASIK group compared to the SMILE group at 1 day postoperatively. Meanwhile, UCVA at 1 week and 1 month postoperatively, showed superior results in the SMILE group. Residual refractive error at 1 month postoperatively also showed better results in SMILE than FS-LASIK.